Pressure-sensitive adhesive powder. Issue 1 (8th October 2015) - Fujii, S.; Sawada, S.; Nakayama, S.; Kappl, M.; Ueno, K.; Shitajima, K.; Butt, H.-J.; Nakamura, Y.
Abstract : Pressure-sensitive adhesive powder shows no adhesion in its original form and shows its adhesive nature after application of shear stress. Abstract : Pressure-sensitive adhesive (PSA) powder consisting of particles with an adhesive polymer core and a hard nanoparticle shell morphology have been synthesized based on liquid marble technology. The PSA shows no adhesion in its original form, and shows its adhesive nature only after application of shear stress.